2020
DOI: 10.3390/w12030657
|View full text |Cite
|
Sign up to set email alerts
|

Coupling SWAT Model and CMB Method for Modeling of High-Permeability Bedrock Basins Receiving Interbasin Groundwater Flow

Abstract: This paper couples the Soil and Water Assessment Tool (SWAT) model and the chloride mass balance (CMB) method to improve the modeling of streamflow in high-permeability bedrock basins receiving interbasin groundwater flow (IGF). IGF refers to the naturally occurring groundwater flow beneath a topographic divide, which indicates that baseflow simulated by standard hydrological models may be substantially less than its actual magnitude. Identification and quantification of IGF is so difficult that most hydrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…It is used to model rainfall runoff at the basin scale [10]. Several global studies have applied the SWAT model to investigate hydrological and water quality processes [45][46][47], the impact of human pressure on water resources [48][49][50], and the consequences of climate change [36,[51][52][53]. The model's GIS interface [54] allows for simple and quick data processing, such as watershed delineation and spatial and tabular data handling.…”
Section: Swat Model Descriptionmentioning
confidence: 99%
“…It is used to model rainfall runoff at the basin scale [10]. Several global studies have applied the SWAT model to investigate hydrological and water quality processes [45][46][47], the impact of human pressure on water resources [48][49][50], and the consequences of climate change [36,[51][52][53]. The model's GIS interface [54] allows for simple and quick data processing, such as watershed delineation and spatial and tabular data handling.…”
Section: Swat Model Descriptionmentioning
confidence: 99%
“…Since the call for papers was announced in March 2019, and after a rigorous peer-review process, six papers have been accepted for publication [1][2][3][4][5][6]. To gain a better insight into the essence of the Special Issue, we offer brief highlights of the published papers below.…”
Section: Contributionsmentioning
confidence: 99%
“…The paper "Coupling SWAT Model and CMB Method for Modeling of High-Permeability Bedrock Basins Receiving Interbasin Groundwater Flow" [3] couples the Soil and Water Assessment Tool model and the chloride mass balance (CMB) method to improve the modeling of streamflow in high-permeability bedrock basins receiving interbasin groundwater flow (IGF), i.e., the naturally occurring groundwater flow beneath a topographic divide contributing to the streamflow. The Castril River basin in southern Spain was the case study chosen.…”
Section: Contributionsmentioning
confidence: 99%
“…The Soil and Water Assessment Tool (SWAT) model [18] is one of the most popular models used at the basin scale. SWAT has been widely applied in numerous studies around the world to resolve several processes, such as water balance, climate and land-use changes, agricultural pollution from nonpoint sources, and land management [19][20][21][22][23][24]. Recent SWAT studies [1,17,25,26] showed a growing trend towards the use of alternatives to rain gauge networks.…”
Section: Introductionmentioning
confidence: 99%